COMPARISON OF REACTOGENICITY AND IMMUNOGENICITY OF LIVE VACCINES AGAINST INFECTIOUS LARYNGOTRACHEITIS - S. A. Pokhvalny; M. S. Kukushkina; V. Yu. Kulakov; N. V. Moroz; N. A. Perevozchikova (Ветеринария сегодня)
Humoral immune response and ciliary activity of tracheal mucosa of poultry, vaccinated against infectious laryngotracheitis using ciliostatic test, was studied. Regardless of the vaccination route the vaccines decreased the ciliary activity by 5–9 % on Days 3 to 7 post vaccination. Herewith the vaccine ocular application in some chicks induced oneeye serous conjunctivitis, which resolved subsequently. Oral vaccination did not cause any clinical changes. Serological monitoring revealed an earlier and stronger immunity in poultry vaccinated by ocular route. The required seroprotection level in test groups was higher than the minimal value (80%) starting from Day 16 post vaccination. The period of immunity development after oral vaccination correlated with the vaccine dose volume. Moreover the domestic vaccine was highly competitive with foreign vaccines in immunogenicity and reactogenicity.